2001
DOI: 10.1002/jnr.1245
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of neuronal nicotinic acetylcholine receptors during the early stages of damage by oxidative stress in PC12 cells

Abstract: The mechanism for a large loss of neuronal nicotinic acetylcholine receptors (nAChRs) in brains with neurodegenerative diseases remains unclear. Based on our previous results of [(3)H]epibatidine binding influenced by lipid peroxidation, we suggest that nAChR deficit in neurodegenerative diseases might be related to the neurons attacked by free radicals. To further understand how free radicals influence the expression of nAChRs, we detected [(125)I]alpha-bungarotoxin binding, nAChR subunit protein and mRNA dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…As just one example, the significant reductions in chrna7, which encodes the α7 nAChR, is consistent with the targeting of this receptor subtype by developmental CPF exposure [95]. Although α7 nAChRs are sparse when compared to the more abundant α4β2 subtype, it is the α7 unit that is overexpressed during brain development [2,15,35,84,115] and is most clearly involved in neuritic outgrowth [19,78], neurotoxicity and neuroprotection [24,40,45,58,103,104]. In addition to the common effect on chrna7, CPF and DZN had substantially disparate actions on a large number of other nAChR genes, with much more widespread consequences for DZN.…”
Section: Cpf and Dzn Effects On Neurotransmitter Systemsmentioning
confidence: 63%
“…As just one example, the significant reductions in chrna7, which encodes the α7 nAChR, is consistent with the targeting of this receptor subtype by developmental CPF exposure [95]. Although α7 nAChRs are sparse when compared to the more abundant α4β2 subtype, it is the α7 unit that is overexpressed during brain development [2,15,35,84,115] and is most clearly involved in neuritic outgrowth [19,78], neurotoxicity and neuroprotection [24,40,45,58,103,104]. In addition to the common effect on chrna7, CPF and DZN had substantially disparate actions on a large number of other nAChR genes, with much more widespread consequences for DZN.…”
Section: Cpf and Dzn Effects On Neurotransmitter Systemsmentioning
confidence: 63%
“…The pretreatment of cultural cells with antioxidants, such as vitamin E and reduced glutathione, can prevent the inhibitory effect of free radicals on The correlation between oxidative stress and the loss of the α4 nAChR subunit has been investigated in the temporal cortex from patients with AD, and the results showed a significant correlation between increased levels of lipid peroxidation and decreased numbers of the α4 nAChR subunit protein in AD brains [17] . In a recent study, we also found that lipid peroxidation induced directly by Aβ might be involved in the deficits of nAChR [48] . In this study, PC12 cells were treated by the addition of 5 mmol/L Aβ [25][26][27][28][29][30][31][32][33][34][35] and Aβ 1-40 , respectively, with or without an antioxidant, vitamin E. An increased lipid peroxidation and significant reductions in [ ]α-BTX binding sites and in the protein levels of the α3 and α7 nAChR subunits were observed in the cells treated with Aβ.…”
Section: Oxidative Stress and Nachrsmentioning
confidence: 70%
“…Aβs damage and kill neurons possibly through an effect on membrane lipid peroxidation, impaired ion-motive ATPases, glucose, and glutamate transporters making nerve cells vulnerable to the excitotoxic effects of glutamate [49] . These findings suggest that lipid peroxidation induced by Aβ might trigger the loss of nAChR in AD [48] . Interestingly, the α7 nAChR subtype may have an antioxidative function.…”
Section: Oxidative Stress and Nachrsmentioning
confidence: 75%
“…AMD is one of the leading causes of irreversible vision loss and blindness in industrialized countries, occurring in about 10-25% of people over 65 years of age (Klein et al, 1992;Zarbin, 1998;Klaver et al, 2001;Chakravarthy et al, 2010). On the other hand, in PC12 cells, it has been demonstrated that during early stages of damage by oxidative stress, there is a reduction in a-bungarotoxin binding sites and expression of nAChRs selectively decreases (Guan et al, 2001).…”
Section: Discussionmentioning
confidence: 99%